The Prevention of Corruption through the Social Crime Prevention - Wayan Widhiasthini, Ni; Luh Yulyana Dewi, Ni; Dewi Sucitawathi P, IGAAG; Nyoman Sri Wisudawati, Ni; Istri Agung Maheswari, AA (International Journal of Psychosocial Rehabilitation, 2020)
One of the corruption prevention models discussed in this study is the Social Crime Prevention, which is a model of preventing crime / corrupt practices through agents of socialization, namely family, playground, mass media and the education system. This research is a qualitative study using sources from books, articles, and journals, and descriptive analysis that describes the process of preventing corruption. The data analysis technique used is the study of literature by collecting, analyzing, and presenting data to provide an overview of corruption prevention. The results of this study indicate that corruption prevention can be done by strengthening individual ties with groups, in this case the main key is the family and the education system.